2015
DOI: 10.1002/bem.21898
|View full text |Cite
|
Sign up to set email alerts
|

Geomagnetic and strong static magnetic field effects on growth and chlorophyll a fluorescence in Lemna minor

Abstract: The geomagnetic field (GMF) varies over Earth's surface and changes over time, but it is generally not considered as a factor that could influence plant growth. The effects of reduced and enhanced GMFs and a strong static magnetic field on growth and chlorophyll a (Chl a) fluorescence of Lemna minor plants were investigated under controlled conditions. A standard 7 day test was conducted in extreme geomagnetic environments of 4 µT and 100 µT as well as in a strong static magnetic field environment of 150 mT. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 81 publications
(115 reference statements)
0
10
0
Order By: Relevance
“…As a result, it was shown that pre-sowing magnetic treatment improves the accumulation of biomass in soybeans. Jan et al (2015) in the article examined influence of the MF on growth and Chl a fluorescence of Lemna minor plants under controlled conditions in extreme geomagnetic environments of 150 mT [113]. According to the authors, strong MF affects the increase of initial Chl a fluorescence and energy dissipation in tested plants [30,111].…”
Section: Stimulation Of Seeds Germination By the Mfmentioning
confidence: 99%
“…As a result, it was shown that pre-sowing magnetic treatment improves the accumulation of biomass in soybeans. Jan et al (2015) in the article examined influence of the MF on growth and Chl a fluorescence of Lemna minor plants under controlled conditions in extreme geomagnetic environments of 150 mT [113]. According to the authors, strong MF affects the increase of initial Chl a fluorescence and energy dissipation in tested plants [30,111].…”
Section: Stimulation Of Seeds Germination By the Mfmentioning
confidence: 99%
“…The theory that seed priming with SMF can alter different stages of plant growth and development has been supported by various reports. Previous studies have already confirmed the positive effects of SMF on seed germination and further phases of plant growth [Flórez et al, 2010; Shine et al, 2011; Radhakrishnan et al, 2012; Pietruszewski et al, 2013; Radhakrishnan and Ranjitha Kumari, 2013; Maffei, 2014; Jan et al, 2015; Yao and Shen, 2015; Novitskii et al, 2016; Kataria, 2017; Shine et al, 2017; Cheikh et al, 2018; Jyothi et al, 2018]. Moreover, there are some other reports indicating the supportive roles of magnetopriming on plant growth under stressful conditions through improving physiological and phytochemical characteristics [Javed et al, 2011; Anand et al, 2012; Radhakrishnan et al, 2012; Radhakrishnan and Ranjitha Kumari, 2013; Thomas et al, 2013; Roshandel and Azimian, 2015; Baghel et al, 2016, 2018, 2019; Rathod and Anand, 2016; Kataria et al, 2017; Baghel et al, 2018, 2019; Hasan et al, 2019; Kataria et al, 2019].…”
Section: Discussionmentioning
confidence: 84%
“…Yet, various reports have pointed out the effect of SMF on seed germination or further stages of plant growth [among many: Aladjadjiyan, 2002; Flórez et al, 2010; Shine et al, 2011; Pietruszewski et al, 2013; Maffei, 2014; Jan et al, 2015; Yao and Shen, 2015; Novitskii et al, 2016; Kataria, 2017; Shine et al, 2017; Cheikh et al, 2018; Jyothi et al, 2018]. In others, seed priming with electromagnetic treatment has been applied to reduce the injurious effects of abiotic stresses such as drought stress [Javed et al, 2011; Anand et al, 2012; Baghel et al, 2018; Hasan et al, 2019], salt stress [Radhakrishnan et al, 2012; Radhakrishnan and Ranjitha Kumari, 2013; Thomas et al, 2013; Baghel et al, 2016; Rathod and Anand, 2016; Baghel et al, 2019; Kataria et al, 2019], or UV stress [Kataria et al, 2017].…”
Section: Introductionmentioning
confidence: 99%
“…macrocarpon) and Kabuli chickpea ( Cicer arietinum L) seeds for 10 s to an inhomogeneous static magnetic field with peak magnetic field intensity of 136 mT led to a significant increase in the emergence rate index, shoot dry weight, and contents of N, K, Ca, Mg, S, Na, Zn, Fe, and Mn in both seedling varieties [Grewal and Maheshwari, ]. Jan et al [] conducted a standard 7‐day test in a reduced and enhanced geomagnetic environment of 4 and 100 μT as well as in a strong static magnetic field environment of 150 mT. The results showed that the 4 μT field significantly stimulated growth rate, and the 150 mT field seemed to have the potential to increase initial Chl a fluorescence and energy dissipation in Lemna minor plants.…”
Section: Introductionmentioning
confidence: 99%
“…The experiences of other researchers were also used to determine the exposure time schedule. The exposure times were taken to be of the order of 1 h/day [Vashisth and Nagarajan, ; Todorović et al, ; Elferchichi et al, ; Milovanovich et al, ] for several consecutive days [Jan et al, ; Elferchichi et al, ; Milovanovich et al, ]. In the referenced studies, the effects of the magnetic field were shown to be exposure‐dependent; however, a firm correlation between the effect intensity and applied exposure characteristics was not reported.…”
Section: Introductionmentioning
confidence: 99%